Extracción de colágeno tipo I de piel de tilapia (Oreochromis niloticus) por los métodos acuoso y enzimático - Reátegui Pinedo, Nataly Yahayra (2020)
The objective of the investigation was to determine the biological characteristics of the skin's collagen in Oreochromis niloticus “tilapia”, referred to performance, quantification of total proteins, electrophoresis SDS-PAGE, thermal stability, morphology of the surface structure by optical microscopy and the amount of collagen type I obtained by the methods of aqueous soluble collagen (ASC) and by pepsin soluble collagen (PSC). The biological material, tilapia, was obtained at the Experimental Center of Genetics of the National University of Trujillo. The weights of the individuals were recorded and the skin of the fish was extracted and after registering the skin weight of each individual, the collagen was extracted. By the ASC, a pretreatment was carried out with and without sodium hydroxide 0.1M/24h, followed by the application of butanol to 10 %and extraction in acetic acid 0.5M / 24h, and by the PSC, pretreatment with 0.1M / 24h sodium hydroxide followed by treatment with butanol at 10% and extraction in pepsina at 0.1% in acetic acid 0.5M / 48h. After lyophilization, the samples were weighed and characterized. The profile of bands obtained by electrophoresis SDS-PAGE revealed the same for all three types of treatments and for collagen type I of certified cattle (Sigma), the α1 and α2 bands and the β band were visible. The yield of ASC was 20.43% while in PSC it was 22.47%, the total proteins were quantified in greater quantity in ASC without NaOH and in similar amounts in ASC with NaOH and PSC, in relation to the surface structure of the the differences were evident, the most conserved microfibrils in the ASC. The PSC method confirmed the presence of type I collagen in the skin of tilapia (O. niloticus) and in a slightly larger amount of collagen.